A New Solution in Understanding Massive White Dwarfs*Supported by the National Natural Science Foundation of China under Grant Nos 11275073 and 11305063, and the Fundamental Research Funds for the Central Universities under Grant No 2014ZG0036. (May 2016) - Jing 荆, Zhen-Zhen 珍珍; Wen 文, De-Hua 德华
Abstract : The observed high over-luminous type-Ia supernovae imply the existence of super-Chandrasekhar limit white dwarfs, which raises a challenge to the classical white dwarf theories. By employing the Eddington-inspired Born–Infeld (EiBI) gravity, we reinvestigate the structures and properties of white dwarfs, and find out that the EiBI gravity provides a new way to understand the observations. It is shown that by choosing an appropriate positive Eddington parameter κ, a massive white dwarf with mass up to 2.8M⊙ can be supported by the equation of state of free electron gas. Unlike the classical white dwarf theory, the maximum mass of the white dwarf sequence in the EiBI gravity is not decided by the mass–radius relations, but is decided by the central density, ρc = 4.3 × 10 14 kg/m 3, above which neutronization cannot be avoided and the white dwarf will transform into a neutron star. On the other hand, if the gravity in the massive white dwarf really behaves as the EiBI gravity predicts, then one can obtain a constraint on the Eddington parameter in the EiBI gravity, that is, 8πρ0 κG/c 2 ≥ 80 (where ρ0 = 10 18 kg/m 3 ) to support a massive white dwarf with mass up to 2.8M⊙ . Moreover, we find out that the fast Keplarian frequency of the massive white dwarf raises a degeneration between the two kinds of compact stars, that is, one cannot distinguish whether the observed massive pulsar is a massive neutron star or a massive white dwarf only through the observed pulse frequency and mass.